The Efficacy of Leader’s Islamic spiritual Intelligence Toward Employee Emotional Well-being - Rina Hastuti (Ekonomi Syariah IAIN Kudus, 2016)
The objective of this study is to find the evidence for the efficacy of Religiosity on spirituality workplace. The research conducted by measuring the effect of employee’s perspectives of leader’s islamic spiritual intelligence on employee emotional well-being which mediated by the quality of employee spiritual value. The data was collected from the employees of moslem small medium enterprises on cullinary industry in Surakarta. The 75 samples was analyzed by multivariate analysis (Path Analysis) using SPSS 18 Software Program.The Islamic spiritual intelligence is explained by the variables that reflect the Muhammad SAW characters: sidiq (truthfulness), amanah (trustful), tabliq, and fatanah (wisdom). From the empirical research reveal that the employee spiritual value significantly mediating the effect of sidiq and fatanah toward employee’s emotional wellbeing. Meanwhile the variable of amanah and tabliq has no significant effect to employee spiritual value and employee emotional wellbeing. Therefore the higher the islamic spiritual value of leader (sidiq and fatanah) the higher the spiritual value of employee and the better the quality of employee’s emotional wellbeing.